Problematika Rumah Tangga dalam Novel Hanum dan Rangga Berdasarkan Teori Freud - Faizatul Khoiriyah; Mulyadi Bagas Wicaksono; Inayah Alfina Wulandari; Najma Hanina; Mohamad Afrizal (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research analyzes the domestic problems raised in the novel Hanum & Rangga: Faith & the City using the perspective of Freud's theory. This novel depicts various conflicts that married couples often face, especially regarding gender roles, Islamic values, and the dynamics of a pluralist society. The background of the story shows the clash between personal ambition and household obligations experienced by the main characters, Hanum and Rangga, in the context of modern life in New York. This research aims to identify the internal and external conflicts faced by the main characters and understand the self-defense mechanisms used to overcome these problems. The method used is text analysis with a psychoanalytic approach to explore the psychological dynamics of the characters, including aspects of the id, ego and superego, in dealing with domestic conflict. Research findings show that the problems faced reflect the realities of modern domestic relationships, with a focus on the challenges of maintaining a balance between personal, professional and spiritual life. This research makes an important contribution in understanding how literary works can be a medium for reflection on the complexity of family relationships, as well as highlighting the relevance of Islamic values ​​in building harmonious households in the midst of globalization.